THE ROLE AND EFFECT OF ADVERTISING IN POLITICAL COMMUNICATION: THE EXAMPLE OF THE 2017 TURKISH CONSTITUTIONAL AMENDMENT REFERENDUM (Third Sector Social Economic Review, 2024)
A referendum containing 18 articles of constitutional amendment was held in the Republic of Turkey on April 16, 2017. The referendum results were 51.41% yes, 48.59% no. The 2017 Turkish Constitutional Amendment Referendum was a very important event in terms of political communication. In this referendum, the ""yes"" and ""no"" parties used various communication strategies to influence voters. This research aims to examine the Role and Effect of Advertising in Political Communication in the Turkish Constitutional Amendment Referendum held in 2017. The study was conducted using the document review technique, one of the qualitative research methods. Within the scope of the process called document review in academic research, studies such as researching, finding, examining, reading, classifying, summarizing and synthesizing previously published works on the subject of research have been carried out. The result of the referendum held as a result of the study significantly changed the political administration of the Republic of Turkey. With the presidential system, the powers and responsibilities of the President have increased. This situation has led to significant changes in Turkey's domestic and foreign policy.
Keywords: Politics; Communication; Political Communication; Advertising; Referendum; 2017 Turkish Constitutional Amendment